PERTANGGUNGJAWABAN PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA TERORISME DI INDONESIA - GAUTAMA, PUTU GITHA CAESARA; Yudiantara, I Gusti Ngurah Nyoman Krisnadi (Kertha Negara : Journal Ilmu Hukum, 2023)
The aim of writing the article is to find answers to questions regarding the criminal responsibility of children as perpetrators of terrorism in Indonesia and what the government's efforts are to prevent children from falling into criminal acts of terrorism. The research method applied is normative research, centered on the analysis of written legal documents such as laws, court decisions and legal expert opinions using the statute approach. The results show that children's criminal responsibility for terrorism cases is based on the SPPA Law. In the SPPA Law, Article 81 states